2016
DOI: 10.1016/j.brq.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Multimarket contact and performance: Evidence from emerging economies

Abstract: The organizational structure of multinational enterprises (MNEs) is mainly made up of subsidiaries located in emerging and advanced countries. Consequently, they usually compete against the same rivals simultaneously in both emerging and advanced contexts. Multimarket contact (MMC) theory analyzes the competitive dynamics that arise in these situations. However, researchers have paid more attention to the consequences of multimarket contact in developed countries than to its effect in emerging countries. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Different mechanisms have been proposed to explain why a given subunit feels the pressure of being locally responsive in the market, such as regulatory restrictions in the host country and the existence of cultural distance between the parent firm's home country and the subsidiary's location (Yu et al, 2009). Despite these coordination challenges, some researchers have confirmed that MMC reduces the competitive behaviour of multimarket firms in an international context, and that it increases their performance (Domínguez et al, 2016;Yu et al, 2009). Research on MMC has centred on additional factors that could affect the relationship between MMC and competition (see Yu and Canella, 2013, for a review).…”
Section: And Rivalry: the Role Of Spheres Of Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Different mechanisms have been proposed to explain why a given subunit feels the pressure of being locally responsive in the market, such as regulatory restrictions in the host country and the existence of cultural distance between the parent firm's home country and the subsidiary's location (Yu et al, 2009). Despite these coordination challenges, some researchers have confirmed that MMC reduces the competitive behaviour of multimarket firms in an international context, and that it increases their performance (Domínguez et al, 2016;Yu et al, 2009). Research on MMC has centred on additional factors that could affect the relationship between MMC and competition (see Yu and Canella, 2013, for a review).…”
Section: And Rivalry: the Role Of Spheres Of Influencementioning
confidence: 99%
“…For instance, a positive effect of MMC on prices and profits has been found in the airlines industry (Evans and Kessides, 1994;Gimeno and Woo, 1999) and higher volumes of MMC have been associated with greater stability in banks' market shares (Heggestad and Rhoades;1978). Studies on the mobile telecommunications industry have shown a positive relationship between MMC and prices (Busse, 2000) and, more recently, a U-shaped effect of MMC on firms' performance (Domínguez et al, 2016). In contrast, in the global semiconductor industry, Chuang et al, (2018) found an inverted U-shaped effect of MMC on firms' market share.…”
Section: And Performancementioning
confidence: 99%
“…Under the legal directives of the EU institutions, the mobile telecommunications industry has achieved a high penetration rate in these countries because of a common technological standard, GSM, in the first stages of mobile communications. This favoured the creation of strong European mobile multinationals, such as Telefonica and Vodafone, that started operating in the EU markets and that are present in emerging countries as well (Domínguez, Garrido, Orco, 2016).…”
Section: Theoretical Aspects Of Communication Technologies and Telecomentioning
confidence: 99%
“…The intention is not only to survive but to actually strengthen the community. This is achieved by adopting electronic services and communication methods not only to retain the current population but to increase it by structuring an attractive lifestyle of integrated real and virtual services (Domínguez, Garrido, Orco, 2016).…”
Section: Theoretical Aspects Of Communication Technologies and Telecomentioning
confidence: 99%
“…As with any other journal, there have been outliers relating to eventualities that may affect reviewers or authors, which benefit from a superior degree of patience on the part of the Associate Editors and myself. The good news is that the median paper was accepted 352 days after submission, and that – as targeted by our editorial policy – we were able to accept a few papers with only one round of revisions (Domínguez et al, 2016; Rodriguez-Fernandez, 2016). Revisions with two rounds, which was the case for the majority of the papers published, also had fast turnaround times; some of them below 10 months (e.g., Gras-Gil et al, 2016; Koseoglu, 2016).…”
mentioning
confidence: 99%